Modern C for absolute beginners : a friendly introduction to the C programming language - Dmitrović, Slobodan (Apress, 2021)
Learn the C programming language easily and in a straightforward way. This book teaches the basics of C, the C Standard Library, and modern C standards. No previous programming experience is required. C is a language that is as popular today as it was decades ago. C covers a wide variety of domains. It can be used to program a microcontroller, or to develop an entire operating system. This book is an effort to introduce the reader to the C programming language in a concise and easy to follow manner. The author takes you through the C programming language, the Standard Library, and the C standards basics. Each chapter is the right balance of theory and code examples. After reading and using this book, you'll have the essentials to start programming in modern C. What You Will Learn The C programming language fundamentals The C Standard Library fundamentals New C Standards features The basics of types, operators, statements, arrays, functions, and structs The basics of pointers, memory allocation, and memory manipulation Take advantage of best practices in C Who This Book Is For Beginner or novice programmers who wish to learn the C programming language. No prior programming experience is required.